Trening all' Odin Teatret Film I. Trening vocale = vocal training - Odin Teatret Film ([Holstebro, Denmark] : Odin Teatret Film, 1972)
The film focuses on Odin Theatret's use of text as vocal action. It includes work with various body resonators, exercises which engage the voice as an extension of the body, and vocal improvisations based on a stream of personal association.
Distributed in Australia by Contemorary Arts Media
DVD format
Italian dialogue, with English subtitles
Keywords: Odin teatret; Theater -- Denmark; Voice culture -- Study and teaching -- Denmark